TEM study of alpha-damaged plutonium and americium dioxides. Issue 9 (4th March 2015) - Wiss, Thierry; Dieste-Blanco, Oliver; Tacu, Anca; Janssen, Arne; Talip, Zeynep; Colle, Jean-Yves; Martin, Philippe; Konings, Rudy
Abstract: Abstract : Actinide-based nuclear ceramics, oxides particularly, are not only used as fuel in nuclear power reactors (uranium and plutonium) but are also used/envisaged as materials for electrical power sources in space probes (plutonium or americium). These actinides are all alpha-emitters, some having rather short half-lives. As a result of their strong alpha-activity, the actinide-based materials cumulate radiation damage and radiogenic helium. The stability of such materials needs to be assessed and understood for predicting the long-term stability of not only spent fuel in storage/disposal conditions but also of electrical power sources to be used in space probes. This paper describes the specific transmission electron microscope microstructure analyses of aged 238 PuO2, 238 Pu-doped UO2 (to simulate aged spent nuclear fuel), and of 241 AmO2 samples (candidate electrical power source) and makes the correlation of the observed defects with other properties like helium thermal desorption and lattice parameter. It is shown that these fluorite structured materials resist to high alpha-damage levels and can accommodate large quantities of helium.